Tuning the aggregation of silver nanoparticles with carbon dots for the surface-enhanced Raman scattering application. (15th November 2021) - Chen, Mingming; Du, Bowen; Wang, Qian; Zhang, Jiaxin; Zhu, Xiajun; Lin, Zhengyu; Dong, Yongqiang; Fu, FengFu; Yu, Ting
Abstract: Single-layer carbon dots (CDs) are used as capping agents to synthesize silver nanoparticles (AgNPs). The obtained nanohybrids (AgNPs/CDs) can be self-assembled into nanostructures like nanochains (1D-AgNPs/CDs), nanoflats (2D-AgNPs/CDs) or nanobodys (3D-AgNPs/CDs) by simply tuning the amount of added CDs. It is found that CDs play a key role in controlling the aggregation AgNPs/CDs. The formation mechanisms of the AgNPs/CDs aggregates have been discussed. On the basis, the effects of aggregation dimension on the surface plasmon absorption and surface enhanced Raman spectroscopy (SERS) activity of AgNPs/CDs are investigated and discussed. It is found that the aggregation of AgNPs/CDs creates strong localized surface plasmon resonance. Furthermore, the aggregated AgNPs/CDs of different dimension have similar absorption intensity in the range from 500 to 800 nm, which is most commonly used in the surface enhanced Raman spectroscopy (SERS) measurement. The outstanding local electromagnetic field of the aggregated AgNPs and the enrichment effect of the CDs towards the analytes make all the obtained materials to be SERS substrates. In particular, 2D-AgNPs/CDs exhibit an ultrahigh enhancement factor of 4.02 × 10 14 and a good reproducibility during the SERS test, using crystal violet as the model target molecule. The applicability of 2D-AgNPs/CDs in SERS detection is further confirmed by the measurement of trace thiram residual in apple. Graphical abstract: The obtained CDs shelled AgNPs (AgNPs/CDs) can be self-assembled into 1D-, 2D- or 3D-CDs/AgNPs depending on the amount of CDs, and all the CDs/AgNPs aggregations have strong surface enhanced Raman spectroscopy (SERS) activities. Image 1